Return on investment in training and performance improvement - Phillips, Patricia Pulliam; Phillips, Jack J., 1945-; Toes, Klaas (Routledge, 2024)
"The third edition of this bestselling book guides you through a proven, results-based approach to calculating the return on investment in training and performance improvement programs. The ROI Methodology described in the book has evolved into the most used evaluation system in the world. Patti P. Phillips, Jack J. Phillips, and Klaas Toes present the ROI Methodology, a user-friendly approach to showing and proving the value of programs, projects, and initiatives. Based on over 40 years of development and refinement, it is a process that meets the demands currently facing training and performance improvement functions. This third edition expands upon and updates the second edition with chapters thoroughly detailing the application of the ROI Methodology and new and innovative developments. The book provides relevant examples, case studies and worksheets, and solutions to implementation issues. A case study spans the book and takes the reader through each part of the ROI Methodology. Readers can work through the case, step-by-step, exploring the issues uncovered in the chapter and learn how to apply the process in their own organizations. This book continues to be a primary reference for learning how to utilize ROI to show the contribution of training, education, learning systems, performance improvement, and change initiatives throughout organizations. Proven to work as a guide for practitioners, managers, and leaders, the book is also ideal for students of learning and development at graduate and postgraduate levels and individuals involved in executive and professional development programs. A complimentary 500-page book with 25 detailed case studies is available to book purchasers"-- Provided by publisher.
Originally entered under: Jack J. Phillips.
Keywords: Employees -- Training of -- Evaluation -- Handbooks, manuals, etc.; Rate of return -- Handbooks, manuals, etc.; elektronické knihy; electronic books